Improving Teacher Competence in Developing Science, Technology, Engineering, and Mathematics-Based Learning Tools Through in House Training Activities - Surentu, Loddy (Pinisi Journal of Education and Management, 2023)
Students are free to come up with a brilliant idea and make it a reality. This study aims to improve the competence of SMKN 4 Palu teachers in developing STEM-based learning tools. Therefore, this research method is school action research. This research was carried out at SMK Negeri 4 Palu. The object ofthis research is to improve teacher competence. in developing STEM-based learning tools through in House Training (iHT) activities. The procedure of this research is action planning, action execution, observation, and reflection. Data validity using data triangulation. While the data analysis techniques used in this study are qualitative and quantitative data analysis. Qualitative data analysis uses data reduction, data presentation, and conclusions, while quantitative data analysis is carried out by calculating the average performance increase based on scores obtained from observation sheets that have been compiled. The results showed that the implementation of House Training activities has been proven to be able to improve teacher competence at SMK Negeri 4 Palu in developing STEM-based learning tools.